Conflicting interests: readings in social problems and inequality - Heiner, Robert (Oxford University Press)
The sociological imagination : the promise -- Constructing social problems -- An introduction to the sociology of social problems -- The problem of journalism -- The governing class -- The new economic insecurity -- The Copenhagen consensus -- Global inequality and the challenges of reducing extreme poverty -- Women and wealth : a primer -- The payoff from women's rights -- Doubly divided : the racial wealth gap -- School finance : inequality persists -- Double standards in health care -- The way we wish we were : defining the family crisis -- Striking a balance -- More than welcome : families come first in Sweden -- Life without children -- The implicit ideology of criminal justice -- Schools and prisons : how far have we come since Brown v. Board of Education? -- The growth of incarceration in the Netherlands -- First, reduce harm -- Rx drugs -- Reversal of fortune -- The establishment vs. the environment -- The wealth of the poor : managing ecosystems to fight poverty